Mobile healthcare management (asthma) - Ngai, Pui Shing. (2011)
The aim of this project is to produce a functional application to facilitate the interaction between asthma patients and doctor. Usually doctors rely on the patients’ feedback on the effectiveness of the medication during consultation. Such feedbacks are often delayed for a myriad of reasons, making diagnosis difficult and costly.This application provides a channel for asthma patients to provide feedback on the